Is 3D Printing a Threat to Global Trade? The Trade Effects You Didn't Hear About - Freund, Caroline (World Bank, Washington, DC, 2019)
In the mid-2000s, the production of hearing aids shifted almost entirely to 3D printing. Using difference-in-differences and synthetic control methods, this paper examines the effects of this shift on trade flows. The analysis finds that trade increased roughly 60 percent following the introduction of 3D printing. Revealed comparative advantage was reinforced, with exports growing most rapidly for middle- and high-income countries. The analysis also finds that developing countries increased their imports of hearing aids as a result of the innovation, benefitting consumers. As a robustness check, the paper examines 35 products that are partially 3D printed and finds positive and significant effects on trade. The results counter widespread views that 3D printing will shorten supply chains and reduce trade.